2017
DOI: 10.1088/1752-7163/aa7b8e
|View full text |Cite
|
Sign up to set email alerts
|

The detection of hepatocellular carcinoma (HCC) from patients’ breath using canine scent detection: a proof-of-concept study

Abstract: This is the first study to look at the possibility of detecting HCC from breath using canine olfaction. Our results show that this is possible with an accuracy of 78% (p < 0.001 when compared to chance alone), and are thus a proof of concept. Further refinement of the process of detection will be needed before clinical application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…In 2010, Willis et al published a clinical investigation on bladder cancer [8], after having published a proof-of-principle study in 2004 [9]. Subsequent studies have been performed to investigate the ability of dogs to detect colorectal cancer [10], lung [11][12][13], prostate [14][15][16], and liver [17] cancers, and melanoma [18,19]. Regarding other non-infectious diseases, several studies have suggested that dogs can be used as "alert dogs" for diabetic [20][21][22] and epileptic patients [23], to improve patient quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, Willis et al published a clinical investigation on bladder cancer [8], after having published a proof-of-principle study in 2004 [9]. Subsequent studies have been performed to investigate the ability of dogs to detect colorectal cancer [10], lung [11][12][13], prostate [14][15][16], and liver [17] cancers, and melanoma [18,19]. Regarding other non-infectious diseases, several studies have suggested that dogs can be used as "alert dogs" for diabetic [20][21][22] and epileptic patients [23], to improve patient quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have suggested that dogs seem able to detect human diseases [4], such as bladder [5,6], colon [7,8], prostate [9][10][11], and liver [12] cancers, melanoma [13,14], diabetes [15][16][17][18],epileptic fits [19], malaria [20], and bacteriological diseases [21,22]. The high performances of the dogs in these studies encouraged further research [23].…”
Section: Introductionmentioning
confidence: 99%
“…However, the following studies have demonstrated canine cancer detection for cancer screening is promising, feasible, and safe (Table 3) [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Detection threshold has been shown to be as low as 1.5 parts per trillion (ppt) [10]. Trained dogs can successfully discriminate between patients with cancers of skin [11,12], bladder [13], lung [14][15][16][17][18], breast [14,19,20], prostate [20][21][22] ovary [23][24][25], colorectal [19,26], liver [27], uterine cervix [28] from controls on the basis of odors in breath, urine, blood or cell culture medium. However, the canine cancer detection testing for breast cancer using human urine samples has not yet been attempted.…”
Section: Introductionmentioning
confidence: 99%